The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.7205/milmed-d-13-00139
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Epidermal Necrolysis From SuspectedMycoplasma pneumoniaeInfection

Abstract: Introduction: Toxic Epidermal Necrolysis (TEN) is primarily associated with medication use. Presented is a patient with likely Mycoplasma pneumoniae infection and progression to TEN. Case: A 19-year-old male presented with 1-week history of pneumonia like symptoms and prescribed antibiotics for suspected community-acquired pneumonia. Onset of a new rash was noted and antibiotics were discontinued less than 24 hours after initiation. The diffuse, maculopapular, bullous rash with mucosal lesions ultimately reach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…M. pneumoniae also exerts its toxin-like effects through its metabolites, exotoxin and exotoxin-like toxic substances, lipids, lipopolysaccharides and membrane lipoprotein (28). Following the adherence of M. pneumoniae onto the surface of bronchial cells, with the cytoskeleton rearrangement, M. pneumoniae penetrates through the bronchial mucous membranes and releases nuclease and H2O2, which result in swelling, necrosis and a binding of bronchial epithelial cells, slower microvilli movement, structural deformation, and the termination of swinging, thereby inducing the infiltration of lymphocytes, plasma cells and monocytes (22,29).…”
Section: Direct Damage Mechanismsmentioning
confidence: 99%
“…M. pneumoniae also exerts its toxin-like effects through its metabolites, exotoxin and exotoxin-like toxic substances, lipids, lipopolysaccharides and membrane lipoprotein (28). Following the adherence of M. pneumoniae onto the surface of bronchial cells, with the cytoskeleton rearrangement, M. pneumoniae penetrates through the bronchial mucous membranes and releases nuclease and H2O2, which result in swelling, necrosis and a binding of bronchial epithelial cells, slower microvilli movement, structural deformation, and the termination of swinging, thereby inducing the infiltration of lymphocytes, plasma cells and monocytes (22,29).…”
Section: Direct Damage Mechanismsmentioning
confidence: 99%
“…Stevens–Johnson syndrome and TEN are mainly believed to be caused by a drug hypersensitivity reaction, and microbial infection is occasionally indicated as a cause of disease . The basic treatment includes discontinuing the culprit drug, giving fluids, providing nutritional support, maintaining the water and electrolyte balance, and handling skin and mucous membrane peeling with care .…”
Section: Discussionmentioning
confidence: 99%
“…Stevens-Johnson syndrome and TEN are mainly believed to be caused by a drug hypersensitivity reaction, 9,10 and microbial infection is occasionally indicated as a cause of disease. 1 The basic treatment includes discontinuing the culprit drug, giving fluids, providing nutritional support, maintaining the water and electrolyte balance, and handling skin and mucous membrane peeling with care. 11 Our study revealed there to be a high rate of suspected infection before the onset of SJS/TEN (40.7% and 50.0% in the low-and high-dose groups, respectively), and the proportion of patients in whom a single causative drug was identified was reduced.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations